The abolition of the mandatory death penalty in Bangladesh: a comment on Bangladesh Legal Aid and Services Trust v. Bangladesh. (3rd July 2015) - Novak, Andrew
ABSTRACT: In May 2015, the Bangladesh Supreme Court's Appellate Division invalidated the mandatory death penalty for a specific form of aggravated murder. The Appellate Division confirmed a broad Commonwealth consensus that the mandatory death penalty constitutes cruel and degrading punishment, citing jurisprudence from the United States, the English-speaking Caribbean, East Africa, Singapore and India. Although the decision followed the majority rule in the common law world, it is unlikely to transform Bangladesh's capital punishment regime due to the country's professed exceptionalism as it pertains to political crimes, such as the alleged war crimes carried out during the War of Independence with West Pakistan in 1971. Nonetheless, invalidation of the mandatory death penalty accords with international human rights norms and asserts the independence of the judiciary in relation to criminal sentencing matters.